MicroRNA regulation of Toll‐like receptor, RIG‐I‐like receptor and Nod‐like receptor pathways in teleost fish - Qing Chu; Tianjun Xu (Reviews in Aquaculture, 2020)
The innate immune system is the first‐line defence against invading pathogens, and the main molecules involved in recognizing invading pathogens are the pattern recognition receptors. Accumulating evidences have demonstrated that activation and termination of the immune responses are regulated by various layers of regulators and mechanisms. MicroRNAs (miRNAs) are a group of small non‐coding RNAs that emerged as critical component of the complex regulatory networks in fish immune responses. In this review, we have summarized miRNA regulation in teleost fish, which can provide new insights into the regulation of innate immune receptor pathways in fish. Meanwhile, we comprehensively discuss the recent researches on how teleost miRNAs respond to the signalling pathways of innate immune receptors, including Toll‐like receptors, retinoic acid‐inducible gene‐I‐like receptors and Nod‐like receptors.